A construção discursiva da política de resistência nas memórias de Eneida de Moraes - Lima, Renata Guimarães Cabral (2022)
Based on the theoretical assumptions of French semiotics, this work aims to investigate the discursive construction of the politics of resistance in the autobiographical chronicles of the author from Pará Eneida de Moraes (1903 - 1971), tracing the constitution of meaning of texts through the narrative and discursive aspects of Semiotics greimasiana and some approaches to tensive semiotics. Also, it seeks to identify the social voices expressed through this discourse, which point to the presence of a political subject who constantly resists the various deprivations suffered in prison. Chronicles 16 (from the collection Smell Bath – 1962) and Chronic Companions (from the collection Aruanda – 1957) are analyzed. The texts were written in the 1950s and 1960s, but they recall historical facts of Brazilian politics in the 1930s and mark the course of the subject confined in prison, immobilized by repression, but finding ways to survive and resist the imposed coercion. The analysis of the corpus demonstrates that the discourse of resistance, in these texts, is constructed by the uniqueness of social voices that denounce, contest and confront an authoritarian, violent and repressive power system. It is a discourse woven in the actions of struggle movements in favor of a new political organization based on democratic principles, collective actions and freedom of expression. Therefore, the work contributes to the understanding of discursivities that are ideologically located in the field of resistance politics and confrontations with power systems.